2012
DOI: 10.1007/s12185-012-1092-z
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis of acquired bone marrow failure syndrome during childhood using the 2008 World Health Organization classification system

Abstract: Distinguishing hypoplastic myelodysplastic syndrome from aplastic anemia (AA) is challenging. In the present study, Japanese and Chinese pediatric hematologists and pathologists conducted a joint review of bone marrow (BM) smears and trephine biopsies in 100 children with acquired BM failure syndrome, using the criteria proposed in the 2008 edition of the World Health Organization classification of hematopoietic and lymphoid tissues. The final consensus for the diagnoses of 100 children was AA in 29 patients, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 8 publications
2
10
0
Order By: Relevance
“…The clinical relevance of the diagnosis of RCC remains controversial. Our data, and that of Yang et al , showed an association between conventionally diagnosed MAA and RCC (Table ). Because RCC is a subcategory of MDS, it has traditionally been treated with up front HSCT in an attempt to provide curative therapy prior to progression to clonal hematopoiesis or leukemia.…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…The clinical relevance of the diagnosis of RCC remains controversial. Our data, and that of Yang et al , showed an association between conventionally diagnosed MAA and RCC (Table ). Because RCC is a subcategory of MDS, it has traditionally been treated with up front HSCT in an attempt to provide curative therapy prior to progression to clonal hematopoiesis or leukemia.…”
Section: Discussionsupporting
confidence: 85%
“…RCC remains a controversial classification that has not been widely adopted, largely due to limited data on the clinical implications of this diagnosis . The European Working Group of Childhood MDS (EWOG‐MDS) developed histomorphologic criteria to differentiate SAA from hypocellular RCC and demonstrated reproducibility of these criteria .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…None of the RCMD patients had severe hypoplastic BM. 4 In the EWOG-MDS study, 355 patients with RCC were classified as either RCC with decreased cellularity (n=288) or RCC with increased or normal cellularity (n=67). 5 Because the RCMD/RCC ratio (13/58, 0.22)…”
Section: © F E R R a T A S T O R T I F O U N D A T I O Nmentioning
confidence: 99%
“…Differentiating severe aplastic anemia from hypocellular refractory cytopenia of childhood Due to limitations in the reproducibility of the diagnostic criteria and limited data on the clinical implications [29,90], the provisional diagnosis of RCC remains controversial. The WHO defines RCC as (1) dysplasia in one or more hematopoietic lineages or in at least 10 % of cells in one cell line and (2) less than 5 % blasts in the marrow [13].…”
Section: Refractory Cytopenia Of Childhoodmentioning
confidence: 99%